Unusual self-healing of a traumatic pancreatic fistula that persisted for 16 months - Yue, Ping; Meng, Wenbo; Luo, Zhiwen; Lin, Yanyan; Bai, Bing; Ba, Yongjiang; Li, Xun (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Yue P, Meng W, Luo Z, et al. Unusual self-healing of a traumatic pancreatic fistula that persisted for 16 months. Turk J Gastroenterol 2018; 29: 134-5.